Conserved Nonsense-Prone CpG Sites in Apoptosis-Regulatory Genes: Conditional Stop Signs on the Road to cell Death. (January 2013) - Zhao, Yongzhong; Epstein, Richard J.
Methylation-prone CpG dinucleotides are strongly conserved in the germline, yet are also predisposed to somatic mutation. Here we quantify the relationship between germline codon mutability and somatic carcinogenesis by comparing usage of the nonsense-prone CGA (→TGA) codons in gene groups that differ in apoptotic function; to this end, suppressor genes were subclassified as either apoptotic (gatekeepers) or repair (caretakers). Mutations affecting CGA codons in sporadic tumors proved to be highly asymmetric. Moreover, nonsense mutations were 3-fold more likely to affect gatekeepers than caretakers. In addition, intragenic CGA clustering nonrandomly affected functionally critical regions of gatekeepers. We conclude that human gatekeeper suppressor genes are enriched for nonsense-prone codons, and submit that this germline vulnerability to tumors could reflect in utero selection for a methylation-dependent capability to short-circuit environmental insults that otherwise trigger apoptosis and fetal loss.